Capacity Strengthening training: ‘Analysing Economic Linkages Using Social Accounting Matrix’ at OUAT, Bhubaneswar, India - CGIAR Initiative on National Policies and Strategies (CGIAR, 2023)
Odisha University of Agriculture and Technology (OUAT) and IFPRI organized a capacity strengthening training on “Analyzing Economic Linkages using Social Accounting Matrix” on 1st December 2023 in Bhubaneswar, Odisha. Dr. Karl Pauw, Dr. Barun Deb Pal, and Mr. Manmeet Singh Ajmani from IFPRI conducted the training.